Capsular serotype, antibiotics susceptibility and resistance gene profile of Streptococcus pneumoniae from nasal carriage of healthy children in Selangor, Malaysia - Yusuff, Semiat Opeyemi (2022)
Research on pneumococcal carriage epidemiology are very limited in Malaysia and some other developed countries. This is because most study always focus on symptomatic diseases for prevention and control, meanwhile high level of asymptomatic carriage rate is the starting point of pneumococcal infections. This factors interest us to research on pneumococcal carriage rate, its virulence genes, serotypes distribution, antimicrobial susceptibility pattern and macrolide resistance determinant genes. Three hundred and ten nasal swab samples were collected from healthy children of both 5years old and >5years old with the consent of their parents and guardians. The samples were collected from three selected child care centre; kindergarten, orphanage home and refugee school in Selangor and Kuala Lumpur. Sixty isolates of Streptococcus pneumoniae were recovered from all nasal swabs making the carriage rate of 26.3% for 5years old and 10.4% for >5years old children respectively. All isolates were carrying the virulence genes i.e 63.3% (38) of ply and lytA gene whereas 36.7% (22) carrying a single gene of either ply or lytA. Among the 22 single gene carrying isolates, we selected 12 lytA gene isolates for 16s rRNA sequence analysis for further confirmation of Streptococcus pneumoniae strain and only 7 isolates were of Streptococcus pneumoniae strain, making the total carriage isolates 17.7% (55). We successfully serotyped the 55 isolates by multiplex PCR techniques with the following descending prevalence sequence result: 7A/7F, 23F, 19F, 11A/D and 15B/15C. The vaccine serotype was accounted for 71% and the non-vaccine serotype was 29%. Antibiotic susceptibility testing showed cefotaxime and ceftriaxone were the most susceptible antibiotics to Streptococcus pneumoniae with 50.9% and 49% respectively, erythromycin susceptible Streptococcus pneumoniae has 38.2%, penicillin on the other hand has 20% susceptibility rate. Despite penicillin having the highest rate of non-susceptibility (80%), erythromycin has the highest rate of resistance with 43.6%. Further study on macrolide resistance determinant genes revealed mefA gene has the higher rate of 67.2% (37) while ermB gene has 25.5% (14) and mefA+ermB has 7.3% (4). This proved that macrolide resistance gene that highly triggers the high resistance level of erythromycin is mefA. Pneumococcal carriage rate has decreased over time from previous studies. Serotype analysis has shown the importance of vaccinating the children to reduce the carriage rate and infection. Antibiotics of interest on the other hand should always be tested before prescription, so as to avoid misuse, overuse and unsuitable antibiotics. Continuous study is needed to keep track of pneumococcal carriage rate with serotype distribution, and to understand the antibiotics susceptibility pattern. If the resistant rate is higher, it is crucial to analyse the resistance determinant gene with further molecular study for comprehensive knowledge of Streptococcus pneumoniae in Malaysia.